International observational atopic dermatitis cohort to follow natural history and treatment course: TARGET-DERM AD study design and rationale. Issue 11 (27th November 2020) - Abuabara, Katrina; Silverberg, Jonathan I; Simpson, Eric L; Paller, Amy S; Eichenfield, Lawrence F.; Bissonnette, Robert; Krueger, James; Harris, John E.; Dalfonso, Laura; Watkins, Stephanie E; Crawford, Julie M; Thaçi, D; et al.
Abstract : Introduction: As new topical and systemic treatments become available for atopic dermatitis (AD), there is a need to understand how treatments are being used in routine clinical practice, their comparative effectiveness and their long-term safety in diverse clinical settings. Methods and analysis: The TARGET-DERM AD cohort is a longitudinal, observational study of patients with AD of all ages, designed to provide practical information on long-term effectiveness and safety unobtainable in traditional registration trials. Patients with physician-diagnosed AD receiving prescription treatment (topical or systemic) will be enrolled at academic and community clinical centres. Up to 3 years of retrospective medical records, 5 years of prospective medical records, and optional biological samples and patient-reported outcomes will be collected. The primary aims include characterisation of AD treatment regimens, evaluation of response to therapy, and description of adverse events. Ethics and dissemination: TARGET-DERM has been approved by a central IRB (Copernicus Group IRB, 5000 Centregreen Way Suite 200, Cary, North Carolina 27513) as well as local and institutional IRBs. No additional Ethics Committee reviews. Results will be reviewed by a publications committee and submitted to peer-reviewed journals. Trial registration number: NCT03661866, pre-results.